Electrical stimulation therapy and HA/TCP composite scaffolds modulate the Wnt pathways in bone regeneration of critical-sized defects - Helaehil, Júlia Venturini (2023)
Critical bone defects are the most difficult challenges in the area of tissue repair. Polycaprolactone (PCL) scaffolds, associated with hydroxyapatite (HA) and tricalcium phosphate (TCP), are reported to have an enhanced bioactivity. Moreover, the use of electrical stimulation (ES) has overcome the lack of bioelectricity at the bone defect site and compensated the endogenous electrical signals. Such treatments could modulate cells and tissue signaling pathways. However, there is no study investigating the effects of ES and bioceramic composite scaffolds on bone tissue formation, particularly in the view of cell signaling pathway. This study aims to investigate the application of HA/TCP composite scaffolds and ES and their effects on the Wingless-related integration site (Wnt) pathway in critical bone repair. Critical bone defects (25 mm2) were performed in rats, which were divided into four groups: PCL, PCL + ES, HA/TCP and HA/TCP + ES. The scaffolds were grafted at the defect site and applied with the ES application twice a week using 10 µA of current for 5 min. Bone samples were collected for histomorphometry, immunohistochemistry and molecular analysis. At the Wnt canonical pathway, HA/TCP and HA/TCP + ES groups showed higher Wnt1 and β-catenin gene expression levels, especially HA/TCP. Moreover, HA/TCP + ES presented higher Runx2, Osterix and Bmp-2 levels. At the Wnt non-canonical pathway, HA/TCP group showed higher voltage-gated calcium channel (Vgcc), calmodulin-dependent protein kinase II, and Wnt5a genes expression, while HA/TCP + ES presented higher protein expression of VGCC and calmodulin (CaM) at the same period. The decrease in sclerostin and osteopontin genes expressions and the lower bone sialoprotein II in the HA/TCP + ES group may be related to the early bone remodeling. This study shows that the use of ES modulated the Wnt pathways and accelerated the osteogenesis with improved tissue maturation.